Acumulaciones fluviales en la Depresión del Ebro: valoración de la validez de una secuencia general - Julián Andrés, Asunción; Chueca Cía, José Javier (Geographicalia, 2017)
In this work the sequence of fluvial terraces identified in the main courses of the Ebro Basin are exposed as well as the absolute and relative chronology data available at the present moment. Some fundamental factors in the conformation and conservation of these morphologies are analyred, and he validity of a global correlation of fluvial accumulations for the basin from current available information is discussed.
Keywords: Fluvial terraces; evolutive sequences; global correlation; Ebro Basin.